Communication Patterns of Peatland Agro-Tourism “Talaran Setara” Based on Local Wisdom (Qualitative Study in Karya Maju Village, Marabahan District) - Gunawan Wibisono; Marhaeni Fajar Kurniawati; Muzahid Akbar Hayat (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to analyze the Communication Pattern of Talaran Setara Agrotourism Tourism, to analyze in depth what factors are the Supporters and Barriers in carrying out Tourism Communications for Talaran Setara Peatland Agrotourism, to analyze how to create a brand in Talaran Setara Agrotourism. to analyze what creates the emotional connection that causes trust, intimacy, and passion of tourists in Talaran Setara Agrotourism, to analyze what makes tourists visit Talaran Setara Agrotourism. This type of research is field research using a qualitative approach. The research location is Talaran Setara Agrotourism, Karya Maju Village, Marabahan District. The results of this study: The communication pattern of Talaran Setara Agrotourism carried out by Karya Maju Village is by branding on social media, because in the current global era of social media is the most effective medium to quickly introduce something to the wider community, Talaran Setara Agrotourism is a tourist destination in the form of an artificial garden on an area ofapproximately one hectare which is now being visited by many local people, the existence of Talaran Setara Agrotourism can also grow the economy through traders who sell around tourist , cultural and artistic attractions that display art attractions on a regular basis, and foster a sense of love. in culture and the homeland, as well as creating business opportunities such as culinary, opening parking lots, swing rentals, renting children's toys and various types of businesses that can still be developed through the existence of tourist destinations.